Contribution of Mirt Stove Adoption on Women Empowerment and Fuelwood Saving through a Results-based Financing Mechanism - Belachew, Azmera (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study investigates the contribution of the Mirt Improved Cookstove (ICS) on women's empowerment in Gedeb Asassa woreda, focusing on the role of RBF in promoting sustainable cooking technologies. Data from household surveys, focus group discussions, and key informant interviews were analyzed using STATA version 18. The findings demonstrate significant improvements in women's human, financial, social, physical, and natural assets due to ICS adoption. The Mirt stove reduced women's workload, improved health by offering a safer cooking environment, and enhanced economic stability by lowering cooking time and fuel costs. The stove also contributed to environmental sustainability by reducing fuelwood consumption, helping mitigate deforestation. Additionally, the Mirt stove allowed women more time for income-generating activities, improving household income and resource allocation. Factors such as family size, farm land size, proximity to forests, and fuel expenditure were key in influencing ICS adoption. The study underscores the importance of coordinated efforts between government bodies, stakeholders, and local communities to optimize ICS technology dissemination, further empowering women. The Mirt stove serves as a model for future sustainable development initiatives aimed at improving both women's well-being and environmental conservation.